Actividad del volcán Sabancaya (Perú) 2016-2017: observaciones petrográficas y geoquímicas de los depósitos de tefras del 2017 - Manrique Llerena, Nélida (2018)
From 2013 to present-day, the Sabancaya volcano has resumed a new eruptive episode that we have subdivided in two phases: the first phase was characterized by degassing; coincided with the occurrence of five fumarolic vents located on the north flank, and; the second, current phase that started on November 6, 2016, keeps producing ash emissions and ballistic ejecta from columns as high as 5500 m above the crater. Ash particles and ballistic blocks show homogeneous andesitic compositions (59.8-62.8 wt.% SiO2). The mineral association of juvenile rocks includes plagioclase, clinopyroxene, amphibole, biotite and Fe-Ti oxides. Disequilibrium textures have been observed in some phenocrysts, such as sieve texture and overgrowth rim in plagioclase and reaction rims in amphiboles. We attribute these characteristics to a probable recharge process involving a batch of hot mafic magma ascending into the reservoir.